Urea Detection Using Commercial Field Effect Transistors. (1st January 2018) - Silva, G. O.; Mulato, M.
Abstract : We used an easy method to assemble a biosensor using simple and low cost materials. Commercial SnO2 :F thin films were used as the basic sensing part of an extended-gate ion-sensitive field effect transistor. When used as a pH sensor, the oxide film showed a sensitivity of 59 ± 4 mV.pH −1, and linear response in the pH range 2.0 to 10.0. Since urea detection and quantification is important for the control of many pathologies, as proof of concept the samples were further used as platform for urea sensing by immobilizing urease protein onto the surface of the film. For urea sensing, the modified electrodes showed a linear response in the pUrea range of 2.1 to 3.0 (1.00 mM to 7.94 mM, which covers a suitable screening interval for clinical exams) and a sensitivity of 109 ± 3 mV.pUrea −1 . A steady-state was reached after about 60 seconds. Varied pHs and buffer concentrations were also investigated to assess the biosensor behavior toward changes in the environmental conditions. The proposed device could be applied in clinical trials in developing countries as well as in areas hit by natural disasters.